Clinical Evaluation of a Prototype Underwear Designed to Detect Urine Leakage From Continence Pads. Issue 6 (November 2015) - Long, Adele; Edwards, Julia; Worthington, Joanna; Cotterill, Nikki; Weir, Iain; Drake, Marcus J.; van den Heuvel, Eleanor
Abstract : PURPOSE: We evaluated the performance of prototype underwear designed to detect urine leakage from continence pads, their acceptability to users, and their effect on health-related quality of life and psychosocial factors. DESIGN: Prototype product evaluation. SUBJECTS AND SETTING: Participants were 81 women with an average age of 67 years (range, 32-98 years) recruited between October 2010 and February 2012 from outpatient clinics, general practice surgeries, community continence services, and through charities and networks. METHODS: The TACT3 project developed and manufactured a prototype undergarment designed to alert the wearer to a pad leak before it reaches outer clothing or furniture. The study was conducted in 2 stages: a pilot/feasibility study to assess general performance and a larger study to measure performance, acceptability to users, health-related quality of life, and psychosocial impact. Participants were asked to wear the prototype underwear for a period of 2 weeks, keeping a daily diary of leakage events for the first 7 days. They also completed validated instruments measuring lower urinary tract symptoms, health-related quality of life, and psychosocial impact. RESULTS: On average, 86% of the time participants were alerted to pad leakage events. More than 90% thought the prototype underwear was "good" or "OK" and that it would or could give them more confidence. Mean scores for the International Consultation on Incontinence Questionnaire-Urinary Incontinence Short Form indicated no change in the level of symptoms reported before or after the intervention, and no significant changes in health-related quality of life status occurred, except improvement in for travel restrictions. Evaluation via the Psychosocial Impact of Assistive Devices Scale also indicated a positive impact. CONCLUSION: The prototype underwear evaluated in this study was effective and acceptable for 5 out of every 10 wearers. Findings also suggest that the prototype underwear is suitable for women of all ages, dress sizes, and continence severity.